Vietnam : the (last) war the U.S. lost - Allen, Joe, 1960- (Haymarket Books ; Trade distribution in the U.S. through Consortium Book Sales, 2008)
As the United States now faces a major defeat in its occupation of Iraq, the history of the Vietnam War, as a historic blunder for US military forces abroad, and the true story of how it was stopped, take on a fresh importance. Unlike most books on the topic, constructed as specialized academic studies, The (Last) War the United States Lost examines the lessons of the Vietnam era with Joe Allen's eye of both a dedicated historian and an engaged participant in today's antiwar movement. Many damaging myths about the Vietnam era persist, including the accusations that antiwar activists routinely jeered and spat at returning soldiers or that the war finally ended because Congress cut off its funding. Writing in a clear and accessible style, Allen reclaims the stories of the courageous GI revolt; its dynamic relationship with the civil rights movement and the peace movement; the development of coffee houses where these groups came to speak out, debate, and organize; and the struggles waged throughout barracks, bases, and military prisons to challenge the rule of military command. Allen's analysis of the US failure in Vietnam is also the story of the hubris of US imperial overreach, a new chapter of which is unfolding in the Middle East today. Joe Allen is a regular contributor to the International Socialist Review and a longstanding social justice fighter, involved in the ongoing struggles for labor, the abolition of the death penalty, and to free the political prisoner Gary Tyler.